Dynamic behavior of sandwich beams with different compositions of magnetorheological fluid core. Issue 1 (2nd January 2021) - Acharya, Subash; Allien, Vipin J; N P, Puneet; Kumar, Hemantha
ABSTRACT: Magnetorheological fluid (MRF) sandwich beams belong to a class of adaptive beams that consists of MRF sandwiched between two or more face layers and have a great prospective for use in semi-active control of beam vibrations due to their superior vibration suppression capabilities. The composition of MRF has a strong influence on the MRF properties and hence affects the vibration characteristics of the beam. In this work, six MRF samples (MRFs) composed of combination of two particle sizes and three weight fractions of carbonyl iron powder (CIP) were prepared and their viscoelastic properties were measured. The MRFs were used to fabricate different MRF core sandwich beams. Additionally, a sandwich beam with commercially available MRF 132DG fluid as core was fabricated. The modal parameters of the cantilever MRF sandwich beams were determined at different magnetic fields. Further, sinusoidal sweep excitation tests were performed on these beams at different magnetic fields to investigate their vibration suppression behavior. MRF having larger particle size and higher weight fraction of CIP resulted in higher damping ratio and vibration suppression. Finally, optimal particle size and weight fraction of CIP were determined based on the maximization of damping ratio and minimization of weight of MRF. Graphical Abstract: uf0001